Answer:
Explanation:
Y=(X-3) 3+1
1. Flip the way the equation is facing
1+3 (3-x)=Y
2. Add or Subtract
4 (3-x)=Y
3. Do the parentheses
4(-3x)=Y
4. Solve for X ( Undo addition or Subtraction)
(4-4)=0
What ever you do to one side you have to do to the other!
Y-4
Your New Equation Looks Like
-3x= -4 + Y
5. Undo Multiplication
-3x/3= x
What ever you do to one side you have to do to the other!
-4/3 y/3
6. Divide Y
y/3= 3
7. New equation
X= -4/3 + 3
8. Plug in X to the Original Equation
Y=2(-4/3+3) -3 +(3+1)
9. Solve accordingly